2014
DOI: 10.1038/ejcn.2014.134
|View full text |Cite
|
Sign up to set email alerts
|

Healthy diet indicator and mortality in Eastern European populations: prospective evidence from the HAPIEE cohort

Abstract: Background/Objectives Unhealthy diet has been proposed as one of the main reasons for the high mortality in Central and Eastern Europe (CEE) and the former Soviet Union (FSU) but individual-level effects of dietary habits on health in the region are sparse. We examined the associations between the healthy diet indicator (HDI) and all-cause and cause-specific mortality in three CEE/FSU populations. Subjects/Methods Dietary intakes of foods and nutrients, assessed by food frequency questionnaire (FFQ) in the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 34 publications
9
45
1
Order By: Relevance
“…The demonstrated congruent correlations argue against major systematic misrepresentations by our study participants in their responses to the food habits and physical activity questionnaires. Our findings are in accord with previous reports of significant associations between self-reported dietary and exercise data and objective metabolic measurements (32)(33)(34)(35)(36)(37).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The demonstrated congruent correlations argue against major systematic misrepresentations by our study participants in their responses to the food habits and physical activity questionnaires. Our findings are in accord with previous reports of significant associations between self-reported dietary and exercise data and objective metabolic measurements (32)(33)(34)(35)(36)(37).…”
Section: Discussionsupporting
confidence: 93%
“…It is remarkable that, despite the numerous limitations of self-reported data, the subjective responses by our study subjects correlated significantly and congruently with several objective biological measures of cardiometabolic health. Although self-reported behavioral data are often described as "soft" data, congruent associations with objective measures have frequently been reported (30)(31)(32)(33)(34)(35)(36). For example, alcohol abuse screening questionnaire responses are associated with biological measures of alcohol withdrawal symptoms (30), self-reported smoking status is highly correlated with circulating cotinine levels (31), and dietary and physical activity habits have been shown to predict obesity and cardiometabolic risks (32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores using that scale were found to be associated with prolonged survival (by mean 2 years) [24]. Similar observation in the Eastern European population showed an inverse association between HDI scores and CVD and coronary artery disease mortality, with no association with mortality due to other causes [25].…”
Section: Discussionsupporting
confidence: 67%
“…Unhealthy lifestyle such as bad eating habit, a sedentary lifestyle is often described as the hallmark of chronic conditions such as metabolic syndrome, diabetes, and obesity. In a study, Stefler et al, (47)has shown that unhealthy diet is the main culprit to be blamed for the high mortality rate in a European population as a result of cardiovascular disease. On the other hand, a healthy diet might prevent the development of these conditions leading to a better life.…”
Section: Discussionmentioning
confidence: 99%